Introduction - Marco Antonio ORTIZ SANCHEZ (A+BE: Architecture and the Built Environment)
People spend about 60% of their time in their homes: environments in which the person should feel comfortable and be healthy on account of the technical services and systems in their building (Jia, Srinivasan, & Raheem, 2017). The supply of a comfortable environment should be achieved in an energy efficient way, especially if we are to achieve the EU 2020 or 2030 targets of residential energy consumption. However, in spite of the technological advancements and energy efficient technologies that have already been developed to provide comfort, energy consumption is not decreasing at the rate it should (Tsemekidi Tzeiranaki et al., 2019). There are several complex factors affecting energy consumption of which occupant behaviours is one of them, and building systems, services, and products being some of the others. Moreover, the indoor environmental quality (IEQ) field seems to focus mainly on the thermal and other physiological aspects of comfort and energy expenditure. Yet, collaboration of the IEQ field with the fields of energy engineering and social sciences to combine knowledge to have a better grasp of both sides –building and occupant- of the issue of consumption, does not seem to occur (D’Oca, Hong, & Langevin, 2018; Sovacool, 2014). Therefore, the problem that energy savings have not been achieved with the currently available technological developments could be related to the behavioural factors influencing energy consumption.